Morinda citrifolia L.: Phyto-pharmacological perspective review - M. Sreenivasulu, R. Ramasubramania Raja (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Morinda citrifolia is a tree in the coffee family, Rubiaceae. Its native range extends through Southeast Asia, Central America, and Australasia, and the species is now cultivated throughout the tropics and widely naturalised. M. citrifolia L. also called as Noni or Indian mulberry is a small evergreen tree. It is one of the most important traditional Polynesian medicinal plants. The present study was undertaken to review of M. citrifolia for its effects on antioxidant, anti-epileptic, breast cancer prevention, antibacterial effect, liver protective effects, antifungal activity, anti-helmintic activity, anxiolytic activity, estrogenic activity, immunological activity, analgesic activity, hypotensive activity, insecticidal activity, and cancer preventive effect. This plant has also been popular as a source of red, yellow, and purple dyes.